2007
DOI: 10.1097/01.yic.0000224788.21406.c8
|View full text |Cite
|
Sign up to set email alerts
|

Are serum lithium levels related to the polarity of recurrence in bipolar disorders?

Abstract: The primary objective is to test whether the polarity of recurrence (depressive vs manic or mixed), is related to lithium levels. A total of 86 euthymic bipolar patients (DSM-IV) on lithium monotherapy were prospectively followed up for 2.5 years with regular monitoring of both lithium levels and psychopathology. The last lithium level during the free interval that preceded worsening of affective symptoms was related to polarity of symptoms. To account for effects of major confounders, results were corroborate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Some adjustment of the serum concentrations of mood regulators may also be required, as a function of polarity patterns. Lithium concentrations in the lower part of the therapeutic range may be sufficient for the optimal prevention of depressive episodes, whereas higher lithium concentrations, within the therapeutic range, may be required for optimal protection against manic/mixed episodes [37][38][39] .…”
Section: Discussionmentioning
confidence: 99%
“…Some adjustment of the serum concentrations of mood regulators may also be required, as a function of polarity patterns. Lithium concentrations in the lower part of the therapeutic range may be sufficient for the optimal prevention of depressive episodes, whereas higher lithium concentrations, within the therapeutic range, may be required for optimal protection against manic/mixed episodes [37][38][39] .…”
Section: Discussionmentioning
confidence: 99%
“…The serum levels of mood regulators may also require some adjustment according to the polarity patterns. Lithium levels at the lower range of the therapeutic range may be sufficient for the optimal prevention of depressive episodes, whereas higher lithium levels within this range may be required for optimal protection against manic/mixed episodes [11,12]. As some comorbidities may be associated with the polarity (onset and/or predominant), prevention strategies could be anticipated, particularly in terms of suicidal behaviour or substance misuse.…”
Section: Predominant Polaritymentioning
confidence: 98%
“…Lithium concentrations ≤0.6 mmol/L seemed to be ineffective preventing new manic episodes in RCTs , but may be still sufficient to prevent depression (Severus et al 2010). Higher lithium concentrations may not necessarily protect better against depression; a post-hoc analysis of the MAP study found that lithium concentrations preceding reappearance of depressive symptoms were significantly higher than those preceding new manic episodes (Severus et al 2009;Kleindienst et al 2007). Any need to discontinue lithium often poses a problem.…”
Section: Prevention Of Suicide (Psu)mentioning
confidence: 99%